2016
DOI: 10.1136/medethics-2016-103603
|View full text |Cite
|
Sign up to set email alerts
|

Living with the animals: animal or robotic companions for the elderly in smart homes?

Abstract: Although the use of pet robots in senior living facilities and day-care centres, particularly for individuals suffering from dementia, has been intensively researched, the question of introducing pet robots into domestic settings has been relatively neglected. Ambient assisted living (AAL) offers many interface opportunities for integrating motorised companions. There are diverse medical reasons, as well as arguments from animal ethics, that support the use of pet robots in contrast to living with live animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Robopets, a term first coined by Eachus in 2001, are small animal‐like robots which have the appearance and behavioural characteristics of companion animals or pets (Eachus, ). Examples of robopets reported in the literature include a baby harp seal (PARO), a robotic cat (NeCoRo) and a robotic dog (AIBO) (Preuss & Legal, ). Robopets fall under the broader umbrella of socially assistive companion robots, whose use in older adult care has been widely reviewed, but mostly from a quantitative perspective (Bemelmans, Gelderblom, Jonker, & De Witte, ; Mordoch, Osterreicher, Guse, Roger, & Thompson, ; Pu, Moyle, Jones, & Todorovic, ) and often across a broad base of care settings, not specifically residential care (Kachouie, Sedighadeli, Khosla, & Chu, ; Vandemeulebroucke, de Casterle, & Gastmans, ).…”
Section: Introductionmentioning
confidence: 99%
“…Robopets, a term first coined by Eachus in 2001, are small animal‐like robots which have the appearance and behavioural characteristics of companion animals or pets (Eachus, ). Examples of robopets reported in the literature include a baby harp seal (PARO), a robotic cat (NeCoRo) and a robotic dog (AIBO) (Preuss & Legal, ). Robopets fall under the broader umbrella of socially assistive companion robots, whose use in older adult care has been widely reviewed, but mostly from a quantitative perspective (Bemelmans, Gelderblom, Jonker, & De Witte, ; Mordoch, Osterreicher, Guse, Roger, & Thompson, ; Pu, Moyle, Jones, & Todorovic, ) and often across a broad base of care settings, not specifically residential care (Kachouie, Sedighadeli, Khosla, & Chu, ; Vandemeulebroucke, de Casterle, & Gastmans, ).…”
Section: Introductionmentioning
confidence: 99%
“…Appearance is also an important trait of companion robots; robots can be human-like, service-oriented, or animal-like. It has been reported that preference for appearance varies widely among older adults: Some prefer animal-like robots, while others want a humanoid robot [ 19 , 20 , 26 , 39 , 45 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in an empirical study by Hutson, Lim, Bentley, Bianchi-Berthouze, and Bowling (2011) , the participants compared the animal–type robots to house pets and expected them to behave like real animals. The participants also reported feeling responsible for the robot animal’s welfare, although there are concerns regarding well-being of real animals when they are treated by people with dementia as well ( Preuβ & Legal, 2017 ). The robot’s appearance and behavior can lead people to think that they can form adequate replacements for human or animal companionship and interaction.…”
Section: Discussionmentioning
confidence: 99%